Moralizing gods, impartiality and religious parochialism across 15 societies - Lang, Martin; Purzycki, Benjamin G; Apicella, Coren L; Atkinson, Quentin D; Bolyanatz, Alexander; Cohen, Emma; Handley, Carla; Kundtová Klocová, Eva; Lesorogol, Carolyn; Mathew, Sarah; McNamara, Rita A; Moya, Cristina; et al. (Proceedings. Biological sciences, 2019)
The emergence of large-scale cooperation during the Holocene remains a central problem in the evolutionary literature. One hypothesis points to culturally evolved beliefs in punishing, interventionist gods that facilitate the extension of cooperative behaviour toward geographically distant co-religionists. Furthermore, another hypothesis points to such mechanisms being constrained to the religious ingroup, possibly at the expense of religious outgroups. To test these hypotheses, we administered two behavioural experiments and a set of interviews to a sample of 2228 participants from 15 diverse populations. These populations included foragers, pastoralists, horticulturalists, and wage labourers, practicing Buddhism, Christianity, and Hinduism, but also forms of animism and ancestor worship. Using the Random Allocation Game (RAG) and the Dictator Game (DG) in which individuals allocated money between themselves, local and geographically distant co-religionists, and religious outgroups, we found that higher ratings of gods as monitoring and punishing predicted decreased local favouritism (RAGs) and increased resource-sharing with distant co-religionists (DGs). The effects of punishing and monitoring gods on outgroup allocations revealed between-site variability, suggesting that in the absence of intergroup hostility, moralizing gods may be implicated in cooperative behaviour toward outgroups. These results provide support for the hypothesis that beliefs in monitoring and punitive gods help expand the circle of sustainable social interaction, and open questions about the treatment of religious outgroups.
Keywords: Punishment; trest; experimentální hry; Humans; cultural evolution; kooperační chování; parochialism; interpersonální vztahy; Female; religion; Ethnicity; Morals; lidé; náboženství a psychologie; punishing gods; impartiality; ženské pohlaví; Male; Religion and Psychology; supernatural punishment; etnicita; mravy; mužské pohlaví; Games, Experimental; Interpersonal Relations; Cooperative Behavior